Matters of culture - Hanenberg, Peter (2016)
Ten years ago, Alain Touraine famously defined culture as the new paradigm for understanding today’s world. Five years before, Lawrence E. Harrison and Samuel P. Huntington had edited their volume under the heading “Culture Matters: How Values Shape Human Progress”. Arguably, in the 21st century the study of culture represents an emerging and expanding field, dealing with the central challenges of contemporary society. Because the abstract paradigm of culture seems to be the motor of social change, the study of culture has been increasingly showing its multidimensional relevance at the interface of smart development and critical inquiry. Old, new and renewed cultural practices ask for innovative theories and for advanced research methods. In addition, new approaches such as arts based research, connectivism or the examination of big data challenge the hereto overwhelmingly interpretative humanist scholarly practice. For many academics, trained in the traditional humanities disciplines (from art history to literature or philosophy), the study of culture, perhaps a paradigm that is none, continues to bring added complexity and anxiety. How does culture matter in today’s world? How does culture relate to globalization? How does cultural change shape our mind? Which possible worlds does contemporary culture allow for? In which ways do culture, conflict, citizenship and sovereignty correlate? And, finally, how does the study of culture challenge the critical scholarly endeavor of the humanities? The CECC conference “Matters of Culture” discussed the state of the art of this debate and has acted as a gateway to future research.